Applying the E-learning Framework: Evaluating an E-learning Course toward the Improvement of Quality of ODeL Programs - Oruga, Myra D.; Bagos, Jelaine R. (International Journal on Open and Distance e-Learning, 2018)
Anchored on Khan’s Eight-Dimensional E-Learning Framework, this cross-sectional study evaluated IH 213 (Health Promotion for Equity and Sustainable Development) course—an e-learning course under the Diploma in/Master of International Health Program of the Faculty of Management and Development Studies, University of the Philippines Open University. Guided by the Evaluation Dimension of the E-learning Framework, the core objective of the study was to evaluate the course through assessment of international health learners and evaluation of the instruction and the learning environment. Thirty-three (33) international health learners enrolled in the course during the 2nd semester of A.Y. 2016-2017 served as the respondents of the study. The study used the survey research design to gather data from the respondents. Data were analyzed using descriptive statistics. Recommendations were also presented.